Evaluation of Cardiac Markers in Children Undergoing Hematopoietic Stem Cell Transplantation - Ozturk, Gulfer (J Clin Lab Anal, 2014)
BACKGROUND: Early life‐threatening cardiotoxicity and cardiac death have been reported after hematopoietic stem cell transplantation (HSCT). The purpose of the current study was to evaluate cardiac toxicity of conventional chemotherapy followed by HSCT with cardiac markers: heart‐type fatty acid binding protein (H‐FABP), glycogen phosphorylase BB (GPBB), high sensitive C reactive protein (hsCRP) cardiac troponin I, (cTnI), creatine kinase MB (CK‐MB mass) and myoglobin. METHODS: A total of 20 children who underwent HSCT for malignant and non‐malignant diseases were included in this study. Blood samples were collected from all patients in 0th, 7th and 21st day for evaluating these cardiac biomarkers. The patients’ echocardiography was assessment before and after one‐month of HSCT. RESULTS: Serum 21st H‐FABP level was significantly higher when compared with the 0th day H‐FABP level (P < 0.05) . 7th day hsCRP level was significantly higher than 0th and 21st day levels (P < 0.05). Interestingly, 7th day GPBB level was significantly lower than 0th and 21st day levels (P < 0.05). Myoglobin, CK‐MB mass and cTnI biomarkers remained within the reference range in all patients. CONCLUSIONS: This study showed that H‐FABP and hsCRP both seem to be promising markers for evaluation of cardiotoxicity in HSCT process and probably superior to GPBB, cTnI, CK‐MB mass and myoglobin.